Estudio y manejo clínico de menores que conviven con pacientes de tuberculosis pulmonar, Medellín 2010-2011 (2015)
ABSTRACT: Treatment for latent tuberculosis decreases the risk of this infection in children who are household contacts of patients with such disease. Objective: To describe the study and clinical management of children under 5 years of age who were household contacts of pulmonary tuberculosis patients in Medellin, Colombia during the period 2010-2011. Materials and methods: Cross-sectional study. The relationship between socio-demographic and clinical characteristics, and the management of children and index cases was explored. Results: 28.6% were studied with at least chest X rays and tuberculin skin test. Of those who attended clinical evaluation, 7.9% had active tuberculosis; out of the remaining, 19.4% received treatment for latent tuberculosis. The probability of being studied was higher if the household contact had contributory or subsidized health coverage (adjusted OR: 6.7; 95% CI: 1.5-30.5). The opportunity to receive treatment for latent tuberculosis was related to the tuberculin skin test (adjusted OR: 40.2; 95% CI: 2.59-623.6). Conclusion: The household contacts had not been adequately studied, and did not receive the right treatment, so the prevalence of active tuberculosis among them did not decrease. It is necessary to establish a standardized protocol for the management of children living under similar conditions, and to monitor its implementation. Key words: Isoniazid, Latent Tuberculosis, Preschool, Tuberculosis.